Acceptance of Information Technology Security Among Universities: A Model Development Study - Sulhi, Ahmad; Yahaya, Nor Adnan Bin; Subiyakto, Aang (Journal of Applied Data Sciences, 2023)
This study aims to investigate the acceptance model of information technology security among religious higher education institutions in Indonesia, especially focusing on lecturers or lecturers. This study adopts the Unified Theory of Acceptance and Use of Technology 2 (UTAUT2) model with the addition of additional variables, namely security, privacy, and trust. As reflected in various studies of information systems (IS), many IS models are developed by adopting, combining, and adapting previous models. The researcher in this study developed his model based on input-process-output logic as well as processional and causal models of the information systems (IS) success model. The resulting model has a structure with ten variables and 43 indicators. The relationship between variables is explained through 19 influence links. In addition, in the implementation of the study, the authors break down the model into more detailed assessment instrument levels. Although this model development study may have limitations related to the assumptions used and the researcher's understanding, it has the potential to make a theoretical contribution in terms of the proposition of the new model. In addition, it is important to consider transparency in the development of proposed models and data collection instruments presented as practical points for further research in the context of religious higher education institutions in Indonesia.